Regulatory policy and pharmaceutical innovation in the United Kingdom after Brexit: Initial insights - Hofer, Matthias P.; Criscuolo, Paola; Shah, Nilay; Wal, Anne L. J. ter; Barlow, James (Frontiers in Medicine, 2022)
Brexit was presented as an opportunity to promote innovation by breaking free from the European Union regulatory framework for medical technologies. Since the beginning of 2021 the Medicines and Healthcare products Regulatory Agency (MHRA) operates as the stand-alone and independent regulatory agency for the United Kingdom. MHRA remained reliant on EU regulatory decision-making in its first year of independence, especially for novel medicines. MHRA introduced innovation initiatives, which show early promise for quicker authorization of innovative medicines for cancer and other areas of unmet need There is preliminary evidence for significant regulatory delays for a small number of novel medicines in 2021 compared to other international regulatory bodies Longer-term observation and analysis will be needed to show the full impact of post-Brexit pharmaceutical regulatory policy